2018
DOI: 10.1016/j.bcp.2018.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activity of the metabotropic glutamate receptor 2 explored with a whole-cell label-free biosensor

Abstract: Label-free cellular assays using a biosensor provide new opportunities for studying G protein-coupled receptor (GPCR) signaling. As opposed to conventional in vitro assays, integrated receptor-mediated cellular responses are determined in real-time rather than a single downstream signaling pathway. In this study, we examined the potential of a label-free whole cell impedance-based biosensor system (i.e. xCELLigence) to study the pharmacology of one GPCR in particular, the mGlu 2 receptor. This receptor is a ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
(64 reference statements)
2
11
0
Order By: Relevance
“…We have recorded concentrations ranging from 0.6 to more than 5 µM. These glutamate concentrations are in line with those measured in another recent publication (Doornbos et al, 2018). Thus, Clions are pure positive allosteric modulators of the mGlu3 receptor.…”
Section: Discussionsupporting
confidence: 90%
“…We have recorded concentrations ranging from 0.6 to more than 5 µM. These glutamate concentrations are in line with those measured in another recent publication (Doornbos et al, 2018). Thus, Clions are pure positive allosteric modulators of the mGlu3 receptor.…”
Section: Discussionsupporting
confidence: 90%
“…They modeled the VFT domain and went on to show that Cl − ions stabilize the glutamate-induced active state of the extracellular domain of the mGlu 3 receptor and the large basal activity that had for many years been seen was due to chloride mediated positive allosteric modulation effect on low levels of residual glutamate concentrations. This is consistent with other recent reports of mGlu receptor activation being sensitive to residual levels of glutamate [99].…”
Section: Group II Mglu Receptorssupporting
confidence: 94%
“…We reasoned that the difference in luciferase expression obtained comparing cells expressing the reporter with or without expression of the G protein chimeras could represent an index of reporter activation by endogenously expressed G i/o ‐coupled receptors. As a positive control, we co‐transfected GRM2 because of its reported high constitutive activity (Doornbos et al, 2018) (Figure 2b,c). We found that expression of G q ‐based chimeras only produced a negligible amount of NFAT reporter induction (0.1‐fold increase on average) (Figure 2b), whereas we observed an average of 83‐fold increase in CRE‐induced luciferase expression using the G s ‐based chimeras (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%